AT HØRE, AT HØRE EFTER, AT HØRE TIL: Strategier i forbindelse med høretab og høreapparater - Bisgaard, Susanne (Tidsskriftet Antropologi, 2006)
As long as the sense of hearing remains intact, the individual can participate in the negotiation and production of social and cultural values in the contexts to which she or he ascribes a meaning. But what happens when the sounds are muffled? The handling of hearing loss is subject to substantial individual differences – some wish to participate in all social contexts, others wish only to uphold contact to specific segments of the lifeworld. The hard of hearing may be excluded from a number of contexts, but the hearing aid may be a help to retain a position. Some use them in all their waking hours, others only in specific contexts. The difference is due to physiological and technological circumstances, because no two hearing losses are perceived in the same way. Moreover, the technology of the hearing aid may help the user to hear better, but it does not restore natural hearing. Typically, the hard of hearing go through a process, in which the physical hearing loss is related to the lifeworld. In this process the individual moves from being a normal hearing person to being hard of hearing. Being hard of hearing differed for the informants from a wish to participate in social life to an utter loss of one’s functioning and a concern with bodily appearance.